Análise da expressão da Anexina A1 durante processos inflamatórios agudos e infecção por Plasmodium vivax - Borges, Quessi Irias (2017)
Annexin A1 is a 37 kDa protein, associated with the regulation of the processes of phagocytosis, cell signaling, apoptosis and leukocyte migration. Originally described as a cytosolic phospholipase A2 inhibitory protein, annexin A1 may regulate various components of the inflammatory reaction, such as cytokines. We focused on the regulation of the annexin A 1 protein in developmental biology and acute inflammatory processes and malaria infection caused by Plasmodium vivax. In Chapter 1 it is verified in the literature, some studies indicate a relation between the induction of the annexin A1 expression and the presence of special metabolites derived from medicinal plants. The species studied in this work are Carapa guianensis Aublet and Cariniana rubra. In the acute inflammatory experimental model induced by carrageenan, administration of Carapa guianensis oil emulsions (EOCg) significantly increased the expression of annexin A1 in the leukocyte infiltrate, and that this production is involved in the regulation of leukocyte migration. While the administration of the methanolic extract of Cariniana rubra (EMCr) increased the expression of annexin A1, with levels similar to dexamethasone induction. In the second chapter of this thesis we show that, during the infectious process of malaria caused by Plasmodium vivax, there was an increase in the expression of annexin A1 in patients with low parasitemia with Th1 immune response (r2 = 0,92) and also in patients with levels of normal platelets (r2 = 0,95). In patients with thrombocytopenia, there was a reduction in the expression of annexin A1 in a similar way both in patients with Th1 response and in patients with Th2 response. Therefore, it is possible to hypothesize that annexin A1 has a regulatory effect both during acute inflammatory response and in Plasmodium vivax infection.